2016
DOI: 10.1021/acs.joc.6b01523
|View full text |Cite
|
Sign up to set email alerts
|

Original Mitsunobu-Triggered Sequence Involved in a One-Pot Domino Process toward Tetracyclic Systems Bearing a Bis-N,O-acetal Junction

Abstract: Herein is reported an efficient, one-pot domino process through a 1,6-aza-Michael addition-triggered sequence and an original Mitsunobu-type concerted sequence for the synthesis of tetracyclic systems containing a bis-N,O-acetal junction. This methodology led to the construction of four new bonds, the cleavage of three C-O bonds, and the generation of an asymmetric center. Mitsunobu activation afforded final ring closure involving the creation of two bonds, which remains unprecedented among reported Mitsunobu-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…As displayed in Scheme 4, reacting the chromone-based Michael acceptor 1a with 2-aminoethanol coupling partner led to a poor kinetic control because thermodynamic product 2′a was almost exclusively obtained (Scheme 4, entry 1). It is worth mentioning that in one of our previous works, 12 the same reaction was conducted in the presence of the diester 1,6-Michael acceptor, and only the thermodynamic product was observed. This result indicates that the sole modulation of the chromone-based Michael acceptors structure by removing only one ester group is not sufficient to shift the course of the domino process toward a kinetic control.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As displayed in Scheme 4, reacting the chromone-based Michael acceptor 1a with 2-aminoethanol coupling partner led to a poor kinetic control because thermodynamic product 2′a was almost exclusively obtained (Scheme 4, entry 1). It is worth mentioning that in one of our previous works, 12 the same reaction was conducted in the presence of the diester 1,6-Michael acceptor, and only the thermodynamic product was observed. This result indicates that the sole modulation of the chromone-based Michael acceptors structure by removing only one ester group is not sufficient to shift the course of the domino process toward a kinetic control.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…9,10 In this perspective, we recently reported access to diverse (poly)heterocyclic structures starting from the same platform of chromone-based Michael acceptors, reacting with various primary amines. In these reported studies, 2-pyridones, 11 dihydro-oxazolopyridines, 12 and indolizines 13 were selectively accessed by acting on the courses of the domino processes involved, through (i) the diversification of the amines coupling partners, (ii) the pertinent modulation of the Michael acceptors structures, and/or (iii) the reactivity tuning induced by external agents such as catalysts, additives, and/or specific reagents (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…20 On the other hand, Wang et al recently reported a microwave assisted multicomponent process for the construction of pyrazolo [3,4-e]indolizines derivatives (Scheme 1c). 21 On the basis of both our previous reports 22,23 and others' contributions, 24−26 the chromone-based Michael acceptor is a highly valuable platform for rapid access to molecules of biological potential such as pyridones, 22 fused iso-oxazolines, 23 pyridines, 24 fused dihydropyridines 25,26 and pyrazoles. 26 In the present study, we used this platform to investigate the feasibility to access the indolizine skeleton.…”
mentioning
confidence: 80%
“…On the basis of both our previous reports , and others’ contributions, the chromone-based Michael acceptor is a highly valuable platform for rapid access to molecules of biological potential such as pyridones, fused iso-oxazolines, pyridines, fused dihydropyridines , and pyrazoles . In the present study, we used this platform to investigate the feasibility to access the indolizine skeleton.…”
mentioning
confidence: 93%